Kalanchoe daigremontiana: Functional Properties and Histopathological Effects on Wistar Rats under Hyperglycemia-inducing Diet - Madariaga-Navarrete, Alfredo; Aquino-Torres, Eliazar; Cariño-Cortés, Raquel; Villagómez-Ibarra, Roberto; Ocampo-López, Juan; Sharma, Ashutosh; Hernández-Fuentes, Alma Delia (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Diabetes is a worldwide pandemic disease with an expensive way of control. Locals around the world have been used botanical extracts to reduce the effects of this deadly disease to improve the quality of life of the patients. Objectives: To evaluate the effects of crude extracts of the ethnobotanical species K. daigremontiana on a hyperglycemia rat model to support its antidiabetic use in traditional medicine. Materials and Methods: Crude leaves extract were daily administered per os to Wistar rats for six months. Hyperglycemic induction model was rich-sucrose diets. Six animals per group were used: i) standard diet, ii) sucrose-rich diet, iii) sucrose-rich diet + extract (1 ml), iv) sucrose-rich diet + extract (2 ml) and v) standard diet + extract (2 ml). All animals were sacrificed and the liver prepared for histopathological analysis. Powdered leaves were functionally characterized and analyzed by Fourier Transform Infrared (FTIR) spectroscopy. Results: Treatment with 2 ml of the crude extract caused the least tissue damage, compared to the control. A high antioxidant activity (DPPH: 111.14 μM Trolox equivalents g-1 dry weight (DW); ABTS: 223.90 μM Trolox equivalents g-1 DW) was observed. A content of 0.54 mg ascorbic acid g-1 DW, total phenol content of 17.45 mg gallic acid g-1 DW and flavonoid content of 2.3 mg equivalent quercetin g-1 DW were determined. No conclusive evidence on the molecules present in the extract was obtained by FTIR spectroscopy. Conclusion: The use of dosages of 2 ml of crude extract of Kalanchoe daigremontiana reduces liver damage under high sucrose conditions.
Keywords: Traditional medicine; Anti-hyperglycemic; Diabetes Sucrose-rich diet; Kalanchoe daigremontiana; Phytotherapy